Macrobotanical remains and shell-midden formation processes, are they related? The case of Poças de São Bento (Portugal) - López-Dóriga, Inés (2018)
The analysis of plant macroremains from Poças de São Bento, a shell-midden in the Sado Valley (Portugal), has provided interesting insights into the shell-midden formation processes and the presence of resources which are often invisible^ in this kind of sites. Preservation and representationissues are discussed in a bidirectional way. Potential complementary explanations for the presence of such plant remains in hunter-gatherer open-air sites are offered. The understanding of plant exploitation patterns by these last huntergatherers in Portugal is crucial for the comprehension of the multifaceted phenomena of Neolithisations, in this case, characterised by a long availability phase and ultimate adoption of domesticates.